Weight-based disparities in perinatal care: quantitative findings of respect, autonomy, mistreatment, and body mass index in a national Canadian survey - Nisha Malhotra; Cecilia M. Jevitt; Kathrin Stoll; Wanda Phillips-Beck; Saraswathi Vedam; the RESPCCT Study Team (BMC Pregnancy and Childbirth)
Abstract Background Qualitative studies document episodes of weight-related disrespectful care, particularly for people with high body mass index (BMI ≥ 30) and reveal implicit and explicit biases in health care providers. No large quantitative studies document the pervasiveness of weight stigma or if experiences change with increasing BMI. Methods The multi-stakeholder RESPCCT study team designed and distributed a cross-sectional survey on the experiences of perinatal services in all provinces and territories in Canada. From July 2020 to August 2021, participants who had a pregnancy within ten years responded to closed and open-ended questions. Chi square analysis assessed differences in mean scores derived from three patient-reported experience measures of autonomy (MADM), respect (MOR), and mistreatment (MIST). Controlling for socio-demographic factors, multivariate logistic regression analysis explored relationships between different BMI categories and respectful care. Results Of 4,815 Canadians who participated, 3,280 with a BMI of ≥ 18.5 completed all the questions. Pre-pregnancy BMI was significantly associated with race/ethnicity, income sufficiency, and education but not with age. Individuals with higher BMIs were more likely to experience income insufficiency, have lower levels of education, and more frequently self-identified as Indigenous or White. Those with BMI ≥ 35 exhibited notably higher odds of reduced autonomy (MADM) scores, with an unadjusted odds ratio of 1.62 and an adjusted odds ratio of 1.45 compared to individuals with a normal weight. Individuals with BMIs of 25–25.9, 30–34.9, and ≥ 35 exhibited odds of falling into the lower tercile of respect (MOR) scores of 1.34, 1.51, and 2.04, respectively (p < .01). The odds of reporting higher rates of mistreatment (top 33% MIST scores) increased as BMI increased. Conclusions While socio-demographic factors like race and income play significant roles in influencing perinatal care experiences, BMI remains a critical determinant even after accounting for these variables. This study reveals pronounced disparities in the provision of respectful perinatal care to pregnant individuals with higher BMIs in Canada. Data suggest that those with higher BMIs face disrespect, discrimination, and mistreatment. Identification of implicit and explicit weight bias may give providers insight enabling them to provide more respectful care.